2016
DOI: 10.1177/0040517516651104
|View full text |Cite
|
Sign up to set email alerts
|

Designing a smart electrically heated sleeping bag to improve wearers’ feet thermal comfort while sleeping in a cold ambient environment

Abstract: In this study, a novel smart electrically heated sleeping bag was developed by incorporating a proportional–integral–derivative heating control system into a traditional sleeping bag. The smart sleeping bag was aimed to maintain human feet temperature within the thermoneutral range (i.e. 25.0–34.0℃) by automatically adjusting the heat power to the feet region based on real-time human toe temperatures. Subsequently, the performance of the newly developed smart sleeping bag in improving human thermal comfort was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Song et al (2016) found that warming feet was able to elevate foot skin temperatures, promote blood flow, and improve both local and whole body thermal comfort of human body while sleeping in cold environments. The results echoed to the findings of Zhang et al (2017) who also examined a novel smart heating sleeping bag with localized heating at the foot region. Keeping feet warm in a cool environment could maintain both feet and the whole body thermal comfort (Zhang et al, 2015).…”
Section: Literature Reviewsupporting
confidence: 63%
See 2 more Smart Citations
“…Song et al (2016) found that warming feet was able to elevate foot skin temperatures, promote blood flow, and improve both local and whole body thermal comfort of human body while sleeping in cold environments. The results echoed to the findings of Zhang et al (2017) who also examined a novel smart heating sleeping bag with localized heating at the foot region. Keeping feet warm in a cool environment could maintain both feet and the whole body thermal comfort (Zhang et al, 2015).…”
Section: Literature Reviewsupporting
confidence: 63%
“…However, most studies discussed the effect of heating on human body when sleeping or performing office task in indoor temperatures higher than 0 °C, whereas few studies considered the effect of heating in improving thermal comfort of occupational workers in extremely cold environments. Based on the previous studies, it was highly expected that feet heating could improve body thermal comfort in cold environments with temperatures lower than 0 °C (Song et al, 2016; Zhang et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the thermoregulation, the current focus has moved to mattress manipulation [11][12], regarded as a much more efficient approach. A number of strategies have been proposed including an electric heat blanket, or electrically heated sleeping bag [13][14]. These powered temperaturecontrolled facilities may meet the human thermal requirements within the bed microclimate, but they are to some extent dangerous owing to the direct contact with the human body.…”
Section: Instructionsmentioning
confidence: 99%
“…It was reported that graphene heater at upper back heating could increase the temperature and maintain the body temperature better, compared with chest heating. Zhang et al 18 have prepared a smart electrically heated sleeping bag to improve wearer’s thermal foot comfort in a cold ambient environment. The smart sleeping bag was aimed to maintain human feet within the thermoneutral range (25.0–34.0) °C.…”
Section: Introductionmentioning
confidence: 99%